2021
DOI: 10.1177/03000605211060675
|View full text |Cite
|
Sign up to set email alerts
|

Effects of vitamin D on thyroid autoimmunity markers in Hashimoto’s thyroiditis: systematic review and meta-analysis

Abstract: Objective To perform a meta-analysis of randomized controlled trials to evaluate the efficacy of vitamin D supplementation on thyroid autoimmunity markers in Hashimoto’s thyroiditis (HT). Methods This meta-analysis included randomized controlled clinical trials identified by a systematic search of electronic databases (PubMed®, MEDLINE®, EMBASE, The Cochrane Library, China National Knowledge Infrastructure) from inception to August 2020. All studies included patients with HT that received vitamin D supplementa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 33 publications
1
18
0
1
Order By: Relevance
“…On the other hand, a small number of studies,showed no significant association between AITDs and vitamin D deficiency [ 14 17 ]. These pieces of evidence led several researchers to examine the effectiveness of vitamin D supplementation in the prevention/treatment of this group of conditions [ 18 , 19 ]. The results are conflicting, so the potential of vitamin D in thyroid diseases treatmentneeds to be clarified.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, a small number of studies,showed no significant association between AITDs and vitamin D deficiency [ 14 17 ]. These pieces of evidence led several researchers to examine the effectiveness of vitamin D supplementation in the prevention/treatment of this group of conditions [ 18 , 19 ]. The results are conflicting, so the potential of vitamin D in thyroid diseases treatmentneeds to be clarified.…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, no published study has evaluated the quality of RCTs for vitamin D supplement in thyroidautoimmunity based on the CONSORT statement. The most recent study published in December 2021 was a meta-analysis focusing on cases of Hashimoto disease and the evaluation was conducted using the Cochrane CollaborationRisk of Bias tool Statistical analysis [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review and meta-analysis from 2021 which included 8 studies (n = 652) also suggests that vitamin D supplementation for >three months reduces autoantibody titers in patients with HT, although treatment ≤3 months was ineffective [ 32 ]. Another recent systematic review and meta-analysis which included six randomized controlled trials with 330 HT patients also showed that after six months of vitamin D supplementation, TPOAb and TgAb levels significantly decreased as compared with the control group.…”
Section: Micronutrients In Htmentioning
confidence: 99%
“…On the other hand, inadequate dietary Se intake may exacerbate HT [ 2 , 4 , 7 ]. Moreover, recent data demonstrated that vitamin D supplementation may have a beneficial effect on the course of HT [ 27 , 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, the reviews or meta-analyses conducted so far have focused on the importance of selected nutrients in Hashimoto’s disease, i.e., selenium, vitamin D, iodine, gluten, zinc, iron, and goitrogens [ 8 , 10 , 11 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ]. However, current clinical evidence of the effect of the dietary factors on HT is still scanty and inconclusive.…”
Section: Introductionmentioning
confidence: 99%